Transformasi Guru PAI dalam Membentuk Karakter Religius Peserta Didik di Era Generasi Y menuju Generasi Z di SMK PGRI 1 Kediri - Nida’ul Haq Nur Fitria; Ahmad Ali Riyadi; Moh. Irmawan Jauhari (STIKes Ibnu Sina Ajibarang, 2025)
In today's era of rapid globalization and modernization, each generation in Indonesia has distinct characteristics, particularly in their ways of thinking, interacting, and facing life's challenges. Generation Y (millennials) and Generation Z, who are now entering the world of education, have very different mindsets and adaptation methods compared to previous generations. One of the major challenges faced by educators is how to address these differences, particularly in teaching Islamic religious values and shaping students' religious character amidst the rapid development of technology and social dynamics. The transition from Generation Y to Generation Z brings significant changes in the world of education, particularly for Islamic Religious Education (PAI) teachers. Generation Z, more familiar with digital technology and the internet, often has a more interactive and visual learning style. They tend to prioritize fast and easily accessible information, and are more open to global cultural influences. This phenomenon presents new challenges for PAI teachers in delivering Islamic religious learning materials that are contextual, relevant, and easily understood by students. The transformation of PAI teachers in shaping students' religious character in this transitional era requires a deep understanding of existing social, technological, and cultural changes. Islamic Religious Education teachers are not only required to possess in-depth knowledge of religious teachings but also to be able to adapt teaching methods to suit the needs of today's students. For example, the use of digital technology in Islamic religious education can facilitate students' access to various relevant information sources, such as Islamic preaching videos, Islamic learning apps, or e-books that can enhance their understanding.